On the Manufacturers of Biosimilars in Asia. Issue 1 (5th October 2022) - Sheth, Smritie; Vashishta, Laxmikant; Goyal, Rohit; Rathore, Anurag; Chirmule, Narendra
Abstract : Over the past 2 decades, biosimilars have created an opportunity for access to affordable medicines globally. The development process includes robust analytical and functional comparability, equivalent pharmacokinetic profile, and demonstration of lack of any meaningful clinical differences. In this brief opinion article, we offer an overview of the major aspects that are involved in biosimilar development and regulatory requirements in Asia in order to facilitate a standardized process that can enable cost‐effective development of biosimilars.